Quaking but not parkin is the major tumor suppressor in 6q deleted region in glioblastoma - Aksoy Yasar, Fatma Betul; Shingu, Takashi; Zamler, Daniel B.; Zaman, Mohammad Fayyad; Chien, Derek Lin; Zhang, Qiang; Ren, Jiangong; Hu, Jian (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GBM) is a high-grade, aggressive brain tumor with dismal median survival time of 15 months. Chromosome 6q (Ch6q) is a hotspot of genomic alterations, which is commonly deleted or hyper-methylated in GBM. Two neighboring genes in this region, QKI and PRKN have been appointed as tumor suppressors in GBM. While a genetically modified mouse model (GEMM) of GBM has been successfully generated with Qk deletion in the central nervous system (CNS), in vivo genetic evidence supporting the tumor suppressor function of Prkn has not been established. In the present study, we generated a mouse model with Prkn-null allele and conditional Trp53 and Pten deletions in the neural stem cells (NSCs) and compared the tumorigenicity of this model to our previous GBM model with Qk deletion within the same system. We find that Qk but not Prkn is the potent tumor suppressor in the frequently altered Ch6q region in GBM.